2015
DOI: 10.1016/j.ejvs.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3, Carotid Plaque Vulnerability, and Potential Effects of Statin Therapy

Abstract: A low galectin-3 intra-plaque concentration seems to correlate with clinically and ultrasonically defined unstable human carotid plaques. Long term statin treatment may induce increase of intra-plaque galectin-3 concentration mediating plaque stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 19 publications
(21 reference statements)
0
35
0
Order By: Relevance
“…This disease process, known as atherothrombosis, can lead to ACS or stroke [17][18][19]. The influence of Gal-3 on both atherosclerotic plaque formation and destabilization has been confirmed in several studies [20][21][22].…”
Section: Galectin-3 and Atherosclerosismentioning
confidence: 99%
“…This disease process, known as atherothrombosis, can lead to ACS or stroke [17][18][19]. The influence of Gal-3 on both atherosclerotic plaque formation and destabilization has been confirmed in several studies [20][21][22].…”
Section: Galectin-3 and Atherosclerosismentioning
confidence: 99%
“…Although most of the attention in the research literature on the carbohydrate-binding lectin Galectin-3 has focused on cardiovascular pathology [1] , especially in heart failure [2] , there have been some recent studies discussing its role in cerebrovascular disease [3,4] . However, the results of these studies have not been completely consistent with each other [5][6][7][8] , and awareness in the neurosciences community about this biomarker remains limited.…”
Section: Introductionmentioning
confidence: 84%
“…On the tissue level, it has been found that Galectin-3 levels are upregulated in particularly unstable regions of the carotid plaques [29] . A somewhat contradictory finding came from Kadoglou et al, who found that intraplaque Galectin-3 levels were lower in symptomatic patients with carotid atherosclerosis, than those who were asymptomatic [6] . Of note, higher intra-plaque Galectin-3 levels were associated with echogenicity of the plaques, and symptomatic patients had MED ONE 2018, 3: e180009 | Email: mo@qingres.com October 17, 2018 3 less echogenic plaques, which might have been a confounding factor.…”
Section: Ischemic Strokementioning
confidence: 97%
“…The methodology has been described previously. 41 In total, 4 mm sections from formalin fixed, paraffin embedded samples were deparaffinised, rehydrated, and antigens retrieved (boiling in 10 mM sodium citrate buffer [pH 6] with 0.05% Tween-20 for 20 min in a microwave oven, slow cool back to room temperature). Samples were washed (three times for 10 min in phosphate buffered saline) and transferred to immunostaining cassettes.…”
Section: Confocal Microscopy Of Immunostained Tissue Sectionsmentioning
confidence: 99%